Tuning the Charge Transport in Nickel Salicylaldimine Polymers by the Ligand Structure - Daniil A. Lukyanov; Vladimir V. Sizov; Alexey I. Volkov; Evgenii V. Beletskii; Andrey N. Yankin; Elena V. Alekseeva; Oleg V. Levin (Molecules, 2022)
The conductivity of the polymeric energy storage materials is the key factor limiting their performance. Conductivity of polymeric NiSalen materials, a prospective class of energy storage materials, was found to depend strongly on the length of the bridge between the nitrogen atoms of the ligand. Polymers obtained from the complexes containing C3 alkyl and hydroxyalkyl bridges showed an electrical conductivity one order of magnitude lower than those derived from more common complexes with C2 alkyl bridges. The observed difference was studied by means of cyclic voltammetry on interdigitated electrodes and operando spectroelectrochemistry, combined with density functional theory (DFT) calculations.